Strategi peningkatkan produktivitas umkm melalui “Sapu Tangan Biru” di Pamekasan - Musoffan, Musoffan; Qamariyah, Siti; Syarif, Moh. (Nur Science Institute, 2024)
This study aims to create a strategy to increase the productivity of MSMEs (Micro, Small, and Medium Enterprises) through the “Sapu Tangan Biru” Program. This program has reduced unemployment, created entrepreneurial opportunities, and increased Gross Regional Domestic Product (GRDP) even during the COVID-19 pandemic. This research method combines qualitative and quantitative methods (mixed methods). Data collection techniques in this study are interviews, observations, and the distribution of questionnaires to respondents. Data analysis in this study uses descriptive analysis techniques both quantitatively and qualitatively. SWOT matrix analysis, both quantitatively and qualitatively, is used in determining its development strategy. The results of this study are several strategies that MSMEs can carry out in the “Sapu Tangan Biru” Program, namely applying the millennial talent up principle, utilizing the development of technological trends, financial management, product innovation, maintaining business legality, and consumer trust. This strategy is in collaboration with the Millennial Talent Up Collaboration. With this strategy, the productivity of MSMEs Sapu Tangan Biru in Pamekasan can increase significantly.